Presentación: El desafío educativo - Iguiñiz Echeverría, Manuel (1993)
For several decades, education constituted for the majority of Peruvians a component of a strategy for the future: one on the access roads to modernization. In recent years, however, educational issues at school and outside of it appear intertwined with the country's major problems and with questions about the type of development possible and desirable for our country.